Toxicological analysis of ambient monitoring in metal industry - Vesna Lazarević; Ivan Krstić; Milovan Dimitrijević (Zaštita Materijala)
Metal industry is the source of many chemical hazards and their synergic effects could damage the health of occupationally exposed population. The application of toxicological analysis in this paper was to investigate the risk of toxic metals and other chemical hazards in the workplace. The aim is to demonstrate and quantify indicators of pollution in the working environment and perceive (realize) the possible health consequences on occupationally exposed population. The subject of research in this paper is the toxicological risk analysis of toxic metals and other chemical hazards in metal industry, based on a survey of ambient monitoring. The applied analytical method is the retrospective epidemiological study type. Identified concentrations of chemical hazards below the limit values, but because exposure time is likely to jeopardize the health status of occupationally exposed population.